2023
DOI: 10.1038/s41531-023-00524-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of women-specific health factors in the severity of Parkinson’s disease

Abstract: Parkinson’s disease (PD) is an age-related neurological disorder known for the observational differences in its risk, progression, and severity between men and women. While estrogen has been considered to be a protective factor in the development of PD, there is little known about the role that fluctuations in hormones and immune responses from sex-specific health experiences have in the disease’s development and severity. We sought to identify women-specific health experiences associated with PD severity, aft… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…S17K ), despite a non-significant group*sex effect in all 3 structures. However, such effect need to be taken carefully as the sex-effect in PD is often correlated with menopause ( 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…S17K ), despite a non-significant group*sex effect in all 3 structures. However, such effect need to be taken carefully as the sex-effect in PD is often correlated with menopause ( 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…on the development and progression of PD. 15 Aside from sex, genetics plays a large role in PD. Genome-wide association studies (GWASs) have identified close to 100 low-penetrance variants associated with PD.…”
Section: Introductionmentioning
confidence: 99%